2022
DOI: 10.1111/ene.15488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination on COVID‐19 outcome in multiple sclerosis

Abstract: Background and purpose COVID‐19 continues to challenge neurologists in counseling persons with multiple sclerosis (pwMS) regarding disease‐modifying treatment (DMT) and vaccination. The objective here was to characterize predictors of COVID‐19 outcome in pwMS. Methods We included pwMS with polymerase chain reaction‐confirmed COVID‐19 diagnosis from a nationwide population‐based registry. COVID‐19 outcome was classified as either mild or severe. Impact of DMT, specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These findings are in line with recent observations from the Austrian MS-COVID-19 investigators who reported a significantly decreased risk for severe illness after developing COVID-19 (defined as the clinical status at the most severe point requiring hospitalization and additionally meeting at least 1 of 5 prespecified and objective respiratory distress criteria) in fully vaccinated patients with MS (OR 0.21). 41 Hesitancy and/or unwillingness to receive vaccination against SARS-CoV-2 ranges between 15% and 30% in patients with MS and is often instilled by safety concerns, despite the fact that the current literature does not show an increased risk for reactogenicity, serious adverse events, or relapse activity. 24 , 25 Our cohort presented with a lower coverage rate, but data collection started well before the rollout of the vaccination campaign in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with recent observations from the Austrian MS-COVID-19 investigators who reported a significantly decreased risk for severe illness after developing COVID-19 (defined as the clinical status at the most severe point requiring hospitalization and additionally meeting at least 1 of 5 prespecified and objective respiratory distress criteria) in fully vaccinated patients with MS (OR 0.21). 41 Hesitancy and/or unwillingness to receive vaccination against SARS-CoV-2 ranges between 15% and 30% in patients with MS and is often instilled by safety concerns, despite the fact that the current literature does not show an increased risk for reactogenicity, serious adverse events, or relapse activity. 24 , 25 Our cohort presented with a lower coverage rate, but data collection started well before the rollout of the vaccination campaign in Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 114, 7 were selected for the final analysis, along with 6 retrieved out from search strategy (Figure 1). References of 13 selected manuscripts 6,7,9,16,17,18,19,20,21,22,23,24 are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the severity of these infections is still unclear, and where cases could be followed on an individual level, there were no deaths from COVID-19 (42, 43). Further research has found that, even after vaccination, pwMS on anti-CD20 drugs were at higher risk of hospitalisation but not death; this risk was not seen with other DMTs including S1PR modulators (44). In our study, 29 individuals across all DMTs contracted SARS-CoV-2 after vaccination and none of these were hospitalised or died.…”
Section: Discussionmentioning
confidence: 99%